2022
DOI: 10.3389/fenvs.2022.911363
|View full text |Cite
|
Sign up to set email alerts
|

Abrupt emission reduction during COVID-19 intensified the spring 2020 rainfall over India

Abstract: The high level of aerosol pollution in South Asia has a measurable impact on clouds, radiation, and precipitation. Here, exploring multiple observational data sets and simulations of the state-of-the-art ECHAM6-HAMMOZ chemistry-climate model, we report that the reduction in anthropogenic emissions during the COVID-19 lockdown period has enhanced precipitation by 5–25% over India. This precipitation enhancement is the result of the combined effect of an enhancement in cloud cover, a reduction in aerosol induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Mazhar et al, (2021) found a significant reduction in Net Solar Radiation (NSR), Net Thermal Radiation (NTR) and Net Radiation (NR) during the global lockdown [17] . Furthermore, various global and regional studies also investigated similar effects of COVID-19 imposed lockdown on Earth's Radiation Budget and stated a clear reduction in terrestrial radiation and air pollution across the world [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] .…”
Section: Covid 19 Lockdown and Earth's Radiation Budgetmentioning
confidence: 99%
“…Mazhar et al, (2021) found a significant reduction in Net Solar Radiation (NSR), Net Thermal Radiation (NTR) and Net Radiation (NR) during the global lockdown [17] . Furthermore, various global and regional studies also investigated similar effects of COVID-19 imposed lockdown on Earth's Radiation Budget and stated a clear reduction in terrestrial radiation and air pollution across the world [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] .…”
Section: Covid 19 Lockdown and Earth's Radiation Budgetmentioning
confidence: 99%